Study to predict noise annoyance level in passenger car cabin interior - Ahmad Kadri, Junoh; Zulkifli, Mohd Nopiah; Mohammad Hosseini, Fouladi; Mohd Jailani, Mohd Nor; Ahmad Kamal, Ariffin (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.